2021
DOI: 10.7150/ijms.48393
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mTOR inhibitor Rapamycin with Torin-2 within the RIST molecular-targeted regimen in neuroblastoma cells

Abstract: The prognosis for patients with relapsed or refractory high-risk neuroblastoma remains dismal and novel therapeutic options are urgently needed. The RIST treatment protocol has a multimodal metronomic therapy design combining molecular-targeted drugs (Rapamycin and Dasatinib) with chemotherapy backbone (Irinotecan and Temozolomide), which is currently verified in a phase II clinical trial (NCT01467986). With the availability of novel and more potent ATP competitive mTOR inhibitors, we expect to improve the RIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The novel multimodal RIST treatment protocol combines two molecular targeted drugs, the mTOR inhibitor Rapamycin and the tyrosine-kinase inhibitor Dasatinib, as a ‘pre-treatment’, with conventional chemotherapeutics, the topoisomerase inhibitor Irinotecan and the alkylating agent Temozolomide ( Figure 4 ). Previous studies in monolayer cultures showed that ‘pre-treatment’ with Rapamycin plus Dasatinib (R+D) synchronizes NB cells in the cell cycle G1 phase and chemosensitizes them towards conventional ‘chemo-treatment’ with Irinotecan plus Temozolomide (I+T) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The novel multimodal RIST treatment protocol combines two molecular targeted drugs, the mTOR inhibitor Rapamycin and the tyrosine-kinase inhibitor Dasatinib, as a ‘pre-treatment’, with conventional chemotherapeutics, the topoisomerase inhibitor Irinotecan and the alkylating agent Temozolomide ( Figure 4 ). Previous studies in monolayer cultures showed that ‘pre-treatment’ with Rapamycin plus Dasatinib (R+D) synchronizes NB cells in the cell cycle G1 phase and chemosensitizes them towards conventional ‘chemo-treatment’ with Irinotecan plus Temozolomide (I+T) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated the beneficial effects of combining FDA approved drugs in treating NB and confirmed that combination studies needed careful planning to provide optimal effectiveness of approved drugs. Another Phase 2 clinical study evaluated the effectiveness of Rapamycin and Dasatinib with Irinotecan and Temozolomide (Waetzig et al, 2021) in NB. This study indicated that combining advanced ATP competitive mTOR inhibitors with this therapeutic protocol resulted in improved outcomes (Waetzig et al, 2021;Xie et al, 2016).…”
Section: Chemotherapymentioning
confidence: 99%
“…Another Phase 2 clinical study evaluated the effectiveness of Rapamycin and Dasatinib with Irinotecan and Temozolomide (Waetzig et al, 2021) in NB. This study indicated that combining advanced ATP competitive mTOR inhibitors with this therapeutic protocol resulted in improved outcomes (Waetzig et al, 2021;Xie et al, 2016). In a Phase 2 clinical study anaplastic lymphoma kinase (ALK) was identified as a potential therapeutic target in NB.…”
Section: Chemotherapymentioning
confidence: 99%
“…Crizotinib monotherapy down-regulated PI3K but not mTOR complex 1 (mTORC1) in cell lines harbouring MYCN amplifications [ 86 ]. The universal mTOR inhibitor Torin-2 effectively inhibited both mTOR complexes [ 87 ]; however, the loss of the feedback mechanisms rescued Akt phosphorylation in ultra-high-risk NBL [ 86 ]. Crizotinib in combination with the dual PI3K-mTOR inhibitor gedatolisib abrogated this Akt activation and also demonstrated effectiveness in less aggressive NBL, for instance, in ALK R1275Q mutated tumours [ 86 ].…”
Section: Combination Therapy In Nbl Treatmentmentioning
confidence: 99%